Equalizing Wage Differences and Bargaining Power: Evidence from a Panel of French Firms - Pierre Cahuc; Christian Gianella; Dominique Goux; André Zylberberg (Institute for the Study of Labor (IZA), 2002)
In this paper, we develop a dynamic model of firm-level bargaining, along the lines of Manning (1993). In this context, we provide a firm level wage equation that explicitly accounts for firm heterogeneity. This wage equation explains inter-firm wage differentials by differences in labour productivity and job turnover. More precisely, our model predicts that the higher the rate of job destruction within one firm, the higher the compensation of workers. We estimate our wage equation using matched employer-employee panel data in the manufacturing sector, where firms are tracked for five years, between 1988 and 1992. The empirical estimates, using GMM techniques, are fully consistent with our theoretical prediction of equalizing differences: workers who take into account their intertemporal discounted income will support lower wages when they benefit from lower unemployment risks within their firm. In our model, wages are set to maximize a Nash bargain criterion, and according to the estimators used or the industry we consider, we show that workers have an average bargaining power between 0.15 and 0.25, measured on a scale going from 0 to 1.
Keywords: J51; J33; 330; collective bargaining; equalizing wage differences; Lohnstruktur; Lohnverhandlungstheorie; Firmentarifvertrag; Schätzung; Verarbeitendes Gewerbe; Frankreich